2017
DOI: 10.5130/ccs.v9i3.5655
|View full text |Cite
|
Sign up to set email alerts
|

Alt_Right White Lite: Trolling, Hate Speech and Cyber Racism on Social Media

Abstract: The rapid growth of race hate speech on the Internet seems to have overwhelmed the capacity of states, corporations or civil society to limit its spread and impact. Yet by understanding how the political economy of the Internet facilitates racism it is possible to chart strategies that might push back on its negative social effects. Only by involving the state, economy and civil society at both the global level, and locally, can such a process begin to develop an effective ‘civilising’ dynamic. However neo-lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Hence, during the pre-electoral period, the political parties were aware of the inevitable necessity to find alliances in other parties as an absolute majority was unlikely to be reached with just the citizens' voting. Figure 13 showed that the overall sentiment trend in our data sample is negative, and this is aligned with the trend in many social networks and communities, where trolling and hate speech are the norm [25]; however, we did report some differences in terms of sentiments as part of the interactions between some parties. For example, in Figure 13a we see a positive sentiment score of PSOE towards UP, and not in vain, the outcome of this election was a coalition government between these two parties.…”
Section: Discussionsupporting
confidence: 77%
“…Hence, during the pre-electoral period, the political parties were aware of the inevitable necessity to find alliances in other parties as an absolute majority was unlikely to be reached with just the citizens' voting. Figure 13 showed that the overall sentiment trend in our data sample is negative, and this is aligned with the trend in many social networks and communities, where trolling and hate speech are the norm [25]; however, we did report some differences in terms of sentiments as part of the interactions between some parties. For example, in Figure 13a we see a positive sentiment score of PSOE towards UP, and not in vain, the outcome of this election was a coalition government between these two parties.…”
Section: Discussionsupporting
confidence: 77%
“…Again, while exposure to social media discrimination was similar in this sample, the Theory of Gendered Prejudice would suggest that men may be exposed to more egregious forms of racist/discriminatory content which may have a stronger or longer‐lasting impact (McDonald, Navarrete, & Sidanius, 2011). This may be probable because men are more likely than women to follow political topics/groups on social media which may function as a platform to post and see more egregious forms of racist/discriminatory content (Jakubowicz, 2017; Park et al, 2016). Finally, some research indicates that men may be more affected by ethnic discrimination because they tend to engage more with perpetrators of racism/ethnic discrimination and respond in more combative forms to assert power (Assari, Moazen‐Zadeh, Caldwell, & Zimmerman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further, extremist, terrorist or radicalising content is hateful content, with the aim of forging an in-group community through shocking, racist and/or discriminatory depictions of an out-group (Bangstad 2014;Lewis 2018). Empirical studies have demonstrated that hateful online content disproportionately affects people of colour (Gardiner et al 2016), women (Chen 2018;Edstrom 2016) and Muslims (Bangstad 2014), and that it discourages these groups from engaging and participating in public discourse, for fear of further intensified hate (Bangstad 2014;Chen 2018;Edstrom 2016;Jakubowicz 2017).…”
Section: Where's Democracy? the Christchurch Call And The Turn To Terrormentioning
confidence: 99%